Genetic variations in APPL2 are associated with overweight and obesity in a Chinese population with normal glucose tolerance - Jiang Shan; Fang Qichen; Yu Weihui; Zhang Rong; Hu Cheng; Dong Kun; Bao Yuqian; Wang Chen; Xiang Kunsan; Jia Weiping (BMC, 2012)
Abstract Background APPL1 and APPL2 are two adaptor proteins, which can mediate adiponectin signaling via binding to N terminus of adiponectin receptors in muscle cells. Genes encoding adiponectin and adiponectin receptors contribute to insulin resistance and the risk of obesity, and genetic variants of APPL1 are associated with body fat distribution. However, the association between genetic variations of APPL2 and metabolic traits remains unknown. In the current study, we aimed to test the impacts of APPL2 genetic variants on obesity in a Chinese population with normal glucose tolerance. Methods We genotyped six single nucleotide polymorphisms (SNPs) in APPL2 in 1,808 non-diabetic subjects. Overweight and obesity were defined by body mass index (BMI). Obesity-related anthropometric parameters were measured, including height, weight, waist circumference, hip circumference. BMI and waist-hip ratio (WHR) were calculated. Results We found significant evidence of association with overweight/obesity for rs2272495 and rs1107756. rs2272495 C allele and rs1107756 T allele both conferred a higher risk of being overweight and obese (OR 1.218, 95% CI 1.047-1.416, p = 0.011 for rs2272495; OR 1.166, 95% CI 1.014-1.341, p = 0.031 for rs1107756). After adjusting multiple comparisons, only the effect of rs2272495 on overweight/obesity remained to be significant (empirical p = 0.043). Moreover, we investigated the effects of these SNPs on obesity-related quantitative traits in all participants. rs2272495 was associated with BMI (p = 0.015), waist circumference (p = 0.006), hip circumference (p = 0.025) as well as WHR (p = 0.047) under a recessive model. Similar associations were found for rs1107756 except for WHR. Conclusion This study suggests that genetic variations in APPL2 are associated with overweight and obesity in Chinese population with normal glucose tolerance.